99mTc-labelled and pH-awakened microbeads entrapping surface-modified lipid nanoparticles for the augmented effect of oxaliplatin in the therapy of colorectal cancer. (16th November 2020) - Rajpoot, Kuldeep; Jain, Sunil K.
Abstract: Aim: This study was aimed to develop Eudragit S100–coated, pH-awakened microbeads (MBs) encapsulating folic acid (FA)-modified tristearin solid lipid nanoparticles (SLNs) loaded with oxaliplatin (OP). Afterward, these formulations were evaluated ( in vitro and in vivo ) for their potential against colorectal cancer (CRC). Methods: The SLNs were synthesised by employing the solvent diffusion technique and then they were entrapped in the MBs. The prepared uncoupled and coupled SLNs (SLN-OP and FA-SLN-OP, respectively) were examined for in vitro cytotoxicity effect against COLO-205. Gamma-scintigraphy study was used for determining biodistribution ( in vivo ) of drug in different organs through MBs. Results: Outcomes for FA-SLN-OP revealed more cytotoxicity (50% inhibitory concentration [IC50 ] = 6.8 µg/ml) against COLO-205 cells ( in vitro ) than OP solution (IC50 = 8.0 µg/ml) and SLN-OP (IC50 = 7.5 µg/ml). MBs were also investigated in vivo using Gamma-scintigraphy study. After 48 h study, 99m Tc-EuB-FA-SLN-OP confirmed an elevated level of drug in the colonic tumour, which was found significantly ( p < 0.0001) higher than that of 99m Tc-EuB-SLN-OP. Conclusions: In conclusion, developed MBs formulation ( 99m Tc-EuB-FA-SLN-OP) suggested promising results against therapy of CRC using dual targeting (i.e. ligand-directed and pH-awakened) approach.